The challenges of teaching English in Malaysia education institutions / Hazwati Hashim - Hashim, Hazwati (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2024)
Expanding on the challenges of teaching English in Malaysia involves considering various factors that influence language education in the country. The historical context of language policies, such as the reintroduction of Science and Mathematics in English and the MBMMBI initiative, reflects the government's efforts to enhance English proficiency. However, challenges persist, including the lack of qualified English teachers, inadequate resources, and students' limited English competence and negative attitudes toward learning the language, particularly in rural areas.